Diet related chronic diseases and the processing, labelling and marketing of food - Shrimpton, Roger; Hawkes, Corinna (2006)
Eating habits and dietary intakes are changing rapidly in the urban areas of the developing world, including in the countries of the Economic Community Of West African States (ECOWAS). Substantial increases in the intakes of fats, refined sugars and salt are leading to imbalanced nutrition and overnutrition. While undernutrition as a public health problem still persists in ECOWAS countries, at the same time chronic diseases are becoming more common. High urbanization rates, shifts to modern technology, and industrialization of the food chain in particular, under the influences of westernization and globalization are accelerating the speed of these changes. While it is recognized that the overnutrition epidemic requires that a concerted multisectoral approach be developed, involving the use of policy, education and trade mechanisms (Chopra et al. 2002), a high priority must also be given to encouraging people to reduce their risks factors, and adopt healthier life styles. The purpose of this paper is to understand the problems and risks associated with the industrialization of the food chain, focusing on the labelling and marketing dimensions of processed foods in relation to the prevention of diet related chronic diseases in the ECOWAS context.